1988
DOI: 10.1530/acta.0.1190277
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II/III and substance P in human follicular fluid obtained during IVF: relation of the peptide content with follicular size

Abstract: Ovarian follicular fluid (FF) of a number of species contain regulatory peptides secreted by granulosa cells or by autonomic nerve terminals. In this report we demonstrate the presence of authentic (HPLC-verification) angiotensin II and III as well as of substance P (SP) in human FF obtained from hMG stimulated infertile patients undergoing in vitro fertilization. Angiotensin II/III (AII/III), estradiol (E2) and progesterone concentrations increase with the size of the follicles. SP concentrations did not vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Administration of an ANG inhibitor in cows avoided the growth of the predominant follicle, and decreased the concentrations of E2 (Ferreira et al 2011). Similarly, in women subjected to ovaric stimulation with human menopausal gonadotropin (HMG), concentrations of ANG were positively correlated with E2 and DPF (Jarry et al 1988). In the current study, correlations between DPF and ANG concentrations were weak.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of an ANG inhibitor in cows avoided the growth of the predominant follicle, and decreased the concentrations of E2 (Ferreira et al 2011). Similarly, in women subjected to ovaric stimulation with human menopausal gonadotropin (HMG), concentrations of ANG were positively correlated with E2 and DPF (Jarry et al 1988). In the current study, correlations between DPF and ANG concentrations were weak.…”
Section: Discussionmentioning
confidence: 99%
“…Near ovulation, the levels of Ang II also increased in the ovary after treating rabbits with hCG (Yoshimura et al 1994), cattle with LH (Acosta et al 2000, Shimizu et al 2007, and women with human menopausal gonadotrophin (hMG) and hCG (Lightman et al 1987). Similarly, Ang II and Ang III were found to be positively correlated with estradiol levels and follicle diameter in women stimulated with hMG (Jarry et al 1988).…”
Section: Regulation Of Ras Members During Follicle Developmentmentioning
confidence: 95%
“…In the pig, the regulation of ovarian angiotensin production may be related to a surge of luteinizing hormone occurring prior to ovulation (Einspanier et al 1991). A link between angiotensins and ovarian steroid synthesis Jarry et al 1988;Palumbo et al 1989), folliculogenesis (Fernandez et al 1985) and ovulation (Pellicer et al 1988;Kuo et al 1991) have been reported. However, the mechanism by which angiotensins affect these processes, particularly ovulation, has not been well defined.…”
Section: Discussionmentioning
confidence: 99%